The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1162/jocn_a_00849
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Capacity Limits Gap Detection during Concurrent Sound Segregation

Abstract: Detecting a brief silent interval (i.e., a gap) is more difficult when listeners perceive two concurrent sounds rather than one in a sound containing a mistuned harmonic in otherwise in-tune harmonics. This impairment in gap detection may reflect the interaction of low-level encoding or the division of attention between two sound objects, both of which could interfere with signal detection. To distinguish between these two alternatives, we compared ERPs during active and passive listening with complex harmonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…First, consistent with previous studies (He, Horwitz, Dubno, & Mills, 1999;Humes et al, 2009Humes et al, , 2010Humes et al, , 2013John, Hall, & Kreisman, 2012;Ozmeral et al, 2016;Snell & Frisina, 2000;Snell, Mapes, Hickman, & Frisina, 2002), GDTs were generally poorer in older participants compared to younger subjects under identical test conditions, where age-related deficits in selective attention could be a factor (Harris et al, 2010). Previous studies suggested that older adults compensated for attentional deficits by relying more on sensory processing (Harris, Wilson, Eckert, & Dubno, 2012;Leung, Jolicoeur, & Alain, 2015 (Harkrider, Plyler, & Hedrick, 2005;Harris & Dubno, 2017;Harris, Mills, He, & Dubno, 2008;Tremblay, Billings, & Rohila, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…First, consistent with previous studies (He, Horwitz, Dubno, & Mills, 1999;Humes et al, 2009Humes et al, , 2010Humes et al, , 2013John, Hall, & Kreisman, 2012;Ozmeral et al, 2016;Snell & Frisina, 2000;Snell, Mapes, Hickman, & Frisina, 2002), GDTs were generally poorer in older participants compared to younger subjects under identical test conditions, where age-related deficits in selective attention could be a factor (Harris et al, 2010). Previous studies suggested that older adults compensated for attentional deficits by relying more on sensory processing (Harris, Wilson, Eckert, & Dubno, 2012;Leung, Jolicoeur, & Alain, 2015 (Harkrider, Plyler, & Hedrick, 2005;Harris & Dubno, 2017;Harris, Mills, He, & Dubno, 2008;Tremblay, Billings, & Rohila, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…The noise conditions (quiet, babble-modulated, and multi-talker babble-modulated noise) were presented in a random order, with a short break between each condition per participant request. Participants watched a muted movie with subtitles during EEG recordings to reduce the effects of attention [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…As stimuli, 0 to 3 silenced gaps are embedded within 6-second white noise. There are ten different gap durations (2,3,4,5,6,8,10,12,15, and 20 ms), and the duration or location of the gaps within the noise is pseudorandomized. As each gap appears six times in each track, a total of 60 gaps were presented.…”
Section: Test Of Auditory Temporal Resolution (Gaps-in-noise Test)mentioning
confidence: 99%
“…The gap detection threshold is known to depend on a variety of stimulus characteristics such as stimulus level, stimulus bandwidth, modulation features, spectral and temporal complexity, and uncertainty [1]. Several evidences suggest that gap detection performance is related to cognitive demand or attentional resources [4][5]. For example, Leung, et al [4] measured auditory event-related potentials during active and passive listening and found that gap detection performance was associated with attentional processing, possibly related to divided attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation